Common pathways to NSSI and suicide ideation: The roles of rumination and self-compassion - Hasking, Penelope; Boyes, Mark; Finlay-Jones, Amy; McEvoy, Peter; Rees, Clare (Routledge, 2018)
OBJECTIVES: We investigated whether rumination and self-compassion moderate and/or mediate the relationships between negative affect and both non-suicidal self-injury (NSSI) and suicide ideation. METHODS: Undergraduate university students (n?=?415) completed well-validated measures of negative affect, rumination, self-compassion, NSSI, and suicide ideation. RESULTS: Neither rumination nor self-compassion moderated associations between negative affect and NSSI and suicide ideation. However, both rumination and self-compassion mediated associations between negative affect and life-time history of NSSI and suicide ideation. Self-compassion additionally mediated the association between negative affect and both 12 month NSSI and suicide ideation. CONCLUSION: The salience of self-compassion, particularly in predicting recent NSSI and suicide ideation, offers promise for early intervention initiatives focusing on less judgmental or self-critical means of self-relation.